Valorizzare il territorio nella prospettiva del bene comune: l’esperienza trentina - Daddi, Denise; Fruet, Caterina (Rivista Italiana di Educazione Familiare, 2024)
The article explores the holistic and circular approach adopted in the Trentino region to promote human ecology, enhance the territory, and ensure children’s well-being. The participatory model, grounded in empathy and sustainability, advocates for the valorization of the territory. Introduced actions foster children’s emotional connection with the region and encourage collective responsibility. The Autonomous Province of Trento and the social cooperative Città Futura, by committing to sustainable development and supporting local small businesses, contribute to the formation of resilient communities focused on collective well-being, reflecting a profound commitment to human ecology and territorial enhancement.